Atividade paranormal e o realismo no cinema de terror contemporâneo - Medeiros, Daniel Lucas de (2017)
The subgenre found footage has proliferated since the turn of the millennium and today represents a significant portion of the production of American horror film - especially the independent one. Characterized by the use of diegetic cameras – inserted within the narrative universe of the films –, which are usually handled by the characters themselves, the productions made within this style approximate the relationship that the public has with a supposedly (and simulated) amateur image and, consequently, more realistic. This dissertation aims to analyze how the subgenre found footage relates to this discussion of film realism, more specifically in horror movies. To achieve this goal, we study the history of film realism - based on studies by authors such as André Bazin, Ismail Xavier and David Bordwell. We discuss the concepts of realism and naturalism, classic cinema and avant-garde cinema, and we see how these discussions fit into our object of study. We also studied the trajectory of found footage, addressing its prehistory (the relationship with literature and radio), the earliest manifestations in the cinema, and its establishment as subgenre of terror after the launch of The Blair Witch Project (1999). The visual and narrative style of found footage is analyzed based on the theories of authors such as Alexandra Heller-Nicholas and Cecilia Sayad. From the information collected in these surveys, we relate the contents to the analysis of the five main films of the horror franchise Paranormal Activity (2009 - 2015). Through these analyzes, we see that the very conception of realism within the franchise proves to be malleable, as films sometimes hang for avant-garde cinema and sometimes for a classic cinema.